O uso de pept??deos antimicrobianos precursores de ceruleina acoplados a pol??meros silk-like no controle de infec????es bacterianas - Sa??de, Amanda Caroline Marques (2016)
Bacteria are becoming resistant to a growing number of conventional antibiotics at a worrisome rate. Therefore, there is an increasing demand for new antimicrobial therapeutics. Antimicrobial peptides (AMPs) are one of promising alternatives for conventional antibiotics and are thought to be less likely to induce resistance. AMPs have been coupled to molecular scaffolds for biomedical applications such as hydrogels for wound dressings and covering implants. Here AMPs were chemically conjugated to the CR4 hydrophilic polymers. The CPF_C1 is a short peptide isolated from Xenopus clivii, the original sequence was modified one called LCPF_C1, aiming to create some distance between the first glycine and the azide added on the N terminus (on the coupled sequence). The conjugation between the AMP and the CR4 polymer used a click chemistry reaction with two steps, dependent of a hetero crosslinker (DBCO???PEG4???NHS Ester). Dynamic light scattering (DLS) and fluorimeter assays were used to evaluate the efficiency of coupling. MALDI-ToF analysis showed 3 molecules of LCPF_C1 peptide for each CR4 polymer. Moreover, microrheology showed changes on hybrids increasing the viscosity. Finally, the compounds were evaluate against four different bacteria: Staphylococcus aureus, Klebsiela pneumoneae carbapenemases (Kpc), Escherichia coli and Pseudomonas aeruginosa. It was possible to observe MIC???s against P. aeruginosa of 11 mM by using the peptide (LCPF_C1) and 55 mM for the original sequence. When the hibrids were compared to the free polymer was not found MIC values against K. pneumoneae (CR-Kp). On the other hand, the hibrids showed three times less activity than the free polymer against P. aeruginosa. No MIC values were found aganst S. aureus. Finally, against E. coli was observed a MIC value of 1000 mM for the free CR4 and 250 mM for the hibrids. On this way, the present work showed the possibility to functionalize biopolymers by using bioactive molecules coupled to biopolimers, changing the physical-chemical characteristics and increasing they applicability against bacterial infections.